Pengaruh Media Pop Up Book Terhadap Kemampuan Membaca Pemahaman Siswa Kelas III SD Negeri 060838 Medan Petisah T.A 2023/2024 - Ismail, Putri Roka; Jheni Yusuf Saragih; Syartika Sri Wahyuni; Feni Bae Zamili (Universitas Sari Mutiara Indonesia, 2024)
The purpose of the study is to determine the effect of pop up book media on students’ reading comprehension ability of third grade students at State Elementary School 060838 Medan Petisah in academic year of 2023/2024. This research is quantitative with experimental methods. The population in this study were third grade students, with a total of 26 students. The data collection techniques were carried out through tests, observations and documentation. The data were analyzed using t-test formula. Based on the t-test table, the results of the Sig (2-tailed) value for the PreTest and Post Test values are 0.000 <0.05, then Ho is rejected and Ha is accepted. So, it can be concluded that there is an influence of pop up book media on students’ reading comprehension ability of third grade students at State Elementary School 060838 Medan Petisah in academic year of 2023/2024.